Feasibility of a low concentration test bolus in CT angiography. Issue 12 (December 2016) - Nijhof, W.H.; Jansen, M.M.; Jager, G.J.; Slump, C.H.; Rutten, M.J.C.M.
Abstract : Aim: To investigate the feasibility of using a low-concentration test bolus in abdominal aorta computed tomography (CT) angiography (CTA). Materials and methods: In 10 patients referred for CTA of the abdominal aorta with a body mass index (BMI) ≤28 kg/m 2, a standard test bolus of 10 ml contrast medium (CM; 350 mg iodine/ml) was compared with a low-concentration test bolus (5 ml CM; 350 mg iodine/ml; 1:1 diluted with saline) in terms of time to peak enhancement (tPE) and peak enhancement (PE). Results: No significant differences were found between the standard and low-concentration test bolus in terms of tPE and PE. Conclusions: A low-concentration test bolus (5 ml, 1:1 diluted with saline) is feasible in patients with a BMI ≤28 kg/m 2 . Highlights: The feasibility of using a low concentration test-bolus was investigated. Lowering the tube voltage increases the enhancement of iodinated contrast medium. The results show that a lower concentration test-bolus is feasible.